An empirical application of lean management techniques to support ETO design and production planning. Issue 11 (2018) - Cannas, V.G.; Pero, M.; Pozzi, R.; Rossi, T.
Abstract: Engineer To Order (ETO) companies have to face the difficulty to manage high uncertainty in customer requirements, and, consequently, to organize all the activities for efficiently and effectively answering customer orders. In these contexts, planning the activities of design, production and assembly departments is a complex task, also given the variability of lead times and the difficulties in forecasting resources workload. Literature has mainly devoted attention to planning tools for standardized make to stock environments, often neglecting ETO companies' needs. This paper aims to present a methodology for supporting design, production and assembly planning in an ETO context. The methodology combines project requirements planning with lean management tools, i.e. Asaichi and visual control and management tools. It has been successfully applied in a company showing its potential for increasing planning performance, company flexibility and, in the end, delivery performance.